THE CONTRIBUTION OF INDONESIAN HADȊTS SCHOLAR MAHFÛZ AL-TERMASI ON TSABAT: A Study of Kifayat al-Mustafid - Daud, Aisyah; Rasyid, Daud; Daud Rasyid, Bilal; Sahyar, Ataullah; Lubis, Asmuliadi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
The hadîts tradition places great emphasis on the precise transmission of reports from reliable sources, with authenticity hinging on the integrity of each link in the chain of transmission (isnâd). This concern for accuracy led narrators to study under authoritative scholars, as the reliability of a hadîts depends significantly on the credibility of its transmitters. Following the compilation of hadîts into canonical texts, students actively pursued learning from recognized teachers, often documenting their scholarly lineages and texts studied in tsabat manuscripts. Many traveled to major centers of Islamic learning, such as the Haramain, where scholars from across the Muslim world gathered. This study examines the contributions of Indonesian hadîts scholars to the tsabat tradition through an analysis of manuscripts by Yasin al-Fadani, Mukhtar 'Atarid al-Bughuri, and Mahfuz al-Termasi. Using a qualitative descriptive approach, it investigates their methods of documentation and transmission. The findings reveal that Indonesian scholars played a vital role in preserving hadîts transmission chains, demonstrating scholarly rigor on par with their Middle Eastern contemporaries. Mahfuz al-Termasi’s Kifâyat al-Mustafîd, in particular, exemplifies meticulous sanad recording. This study underscores the importance of tsabat as a marker of scholarly authenticity and calls for the digitization of such manuscripts to safeuard Islamic intellectual heritage.